Overview of Knowledge of Generation Z Youth Regarding Early Marriage - Entin Srihadi Yanti; Eko Sri Wulaningtyas; Ardina Rezky Noeraini; Jesica Vifera Malega; Pipit Puspitasari (Jurnal Multidisiplin Madani, 2022)
Generation Z youth, born from 1995 to 2010, are national assets that need attention, especially regarding their growth and development (Dewi and Ulfah, 2021). Early marriage is a formal or informal marriage where one of the bride and groom is less than 18 years old (Kemen PPPA, 2020). In 2018, an estimated 1,220,900 children were married before the age of 18 (BPS, 2020). This type of research is a quantitative descriptive which was carried out in October 2022. Data was obtained by distributing online questionnaires to respondents (students) at SMAN 1 Ngadiluwih, Kediri, East Java. Univariate data analysis was carried out to determine the frequency and percentage of research variables. There were 236 respondents involved where 51.69% (122 respondents) were able to answer questions correctly. Adolescent knowledge related to early marriage for Generation Z youth at SMAN 1 Ngadiluwih is in the less category, so it needs to be increased by conducting outreach activities and providing information related to early marriage, especially for Generation Z youth.